2015
DOI: 10.1007/978-3-319-13957-9_9
|View full text |Cite
|
Sign up to set email alerts
|

RNA Quality in Fresh-Frozen Gastrointestinal Tumor Specimens—Experiences from the Tumor and Healthy Tissue Bank TU Dresden

Abstract: The term "pre-analytics" summarizes all procedures concerned with specimen collection or processing as well as logistical aspects like transport or storage of tissue specimens. All or these variables as well as tissue-specific characteristics affect sample quality. While certain parameters like warm ischemia or tissue-specific characteristics cannot be changed, other parameters can be assessed and optimized. The aim of this study was to determine RNA quality by assessing the RIN values of specimens from differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…8 Zeugner et al showed that vacuum-sealing of tissue for short-term storage prior to RNA extraction can minimize the drop in RNA quality. 6 The Genotype-Tissue Expression (GTEx) Consortium reported that RNA quality dropped in samples with longer ischemia times, 2 a finding contrary to Taurianinen 7 and Rudloff 8 ; however, sample types and preservation methods differed between studies.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…8 Zeugner et al showed that vacuum-sealing of tissue for short-term storage prior to RNA extraction can minimize the drop in RNA quality. 6 The Genotype-Tissue Expression (GTEx) Consortium reported that RNA quality dropped in samples with longer ischemia times, 2 a finding contrary to Taurianinen 7 and Rudloff 8 ; however, sample types and preservation methods differed between studies.…”
Section: Introductionmentioning
confidence: 99%
“…2 This is particularly true of the pancreas, where elevated levels of ribonuclease1 (RNAse1), a double-stranded RNA-degrading enzyme, are present. 3–5 For example, when compared to a panel of tissues taken from different donors 6 or the same individual, 2 RNA quality of most pancreas samples were found to be lower than ½ to ¾ of all tissue types tested, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations